Penentuan Kadar Ketoprofen Generik Dan Nama Dagang Dengan Metode Spektrofotometri-UV - Rahmi Ayusasmita Gultom; Anny Sartika Daulay (Jurnal Ilmu Kesehatan dan Gizi, 2023)
Ketoprofen is a non-steroidal anti-inflammatory drug that is used to reduce pain due to inflammation in various rheumatic conditions and degenerative disorders of the skeletal muscle system. In the manufacture of drugs, the examination of the levels of active substances is a requirement that must be met to ensure the quality of the drug. One of the quality requirements is that the content contained must meet the level requirements listed in the Indonesian Pharmacopoeia. The purpose of this study was to determine whether the levels of generic and trade name ketoprofen tablets on the market meet the requirements of the Indonesian Pharmacopoeia levels.This research is descriptive using UV-spectrophotometric method, with 0.1NN NaOH as solvent. The samples used in this study were 4 generic ketoprofen tablets and trade names. The test parameters of this research include Preparation of Standard Parent Solution I (LIB I), Preparation of Solution (LIB II). Determination of maximum wavelength, Determination of linearity of the Calibration Curve and Determination of Ketoprofen levels in tablet preparations. From the test results on samples obtained generic ketoprofen tablets (PT. Hexpharm jaya) of 103.70% ± 0.4280%, ketoprofen tablets with the trade name Kaltropen (PT. Kalbe Farma) of 106.38% ± 0.4879%, tablets Generic ketoprofen (PT. Bernofarm) 102.10%±1.9450%, and generic ketoprofen tablets (PT.Novell) 100.22%±0.8754%. All tablets found met the requirements for the general content, namely the content of the active substance was not less than 99% and not more than 110% of the amount stated on the label.